Kesan Penggunaan Inventori Hafal Quran Mudah & Cepat (Haqat) Terhadap Motivasi Hafazan Al-Quran dalam Kalangan Murid Tahfiz Mubtadi’ (Permulaan) - Fatin Husna Zaidi; Noornajihan Ja‘afar; Muhammad Lukman Ibrahim (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025